The Community Partnership Service Utilization of Social Media for Promoting Binjai Batik Products at UMKM Tan Collection, Binjai District, Binjai City, North Sumatra - Yuyun Yusnida Lase; Andam Lukcyhasnita; Santi Prayudani; Harizahayu; Friendly (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The creative economy serves as a vital platform for promoting and preserving local cultural heritage. UMKM Tan Collection, a creative enterprise producing Binjai's signature